Correction: PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2023)

PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2022)
Acute kidney injury (AKI) is a common severe acute syndrome caused by multiple factors and is characterized by a rapid decline in renal function during a short period. Bone marrow mesenchymal stromal cells (BMSCs) are effective in treating AKI. However, the mechanism of their beneficial effects remains unclear. PTEN-induced kinase 1 (PINK1) may play an important role in kidney tissue repair. In this study, we explored the effect of PINK1 overexpression on enhancing BMSC-mediated repair of AKI. In this study, ischaemia/reperfusion-induced AKI (IRI-AKI) in mice and a hypoxia-reoxygenation model in cells were established, and the indices were examined by pathology and immunology experiments. After ischaemia/reperfusion, PINK1 overexpression reduced apoptosis in injured kidney tissue cell, decreased T lymphocyte infiltration, increased macrophage infiltration, and alleviated the inflammatory response. PINK1 relieved the stress response of BMSCs and renal tubular epithelial cells (RTECs), reduced apoptosis, altered the release of inflammatory factors, and reduced the proliferation of peripheral blood mononuclear cells (PBMCs). In conclusion, BMSCs and RTECs undergo stress responses in response to hypoxia, inflammation and other conditions, and overexpressing PINK1 in BMSCs could enhance their ability to resist these stress reactions. Furthermore, PINK1 overexpression can regulate the distribution of immune cells and improve the inflammatory response. The regulation of mitochondrial autophagy during IRI-AKI maintains mitochondrial homeostasis and protects renal function. The results of this study provide new strategies and experimental evidence for BMSC-mediated repair of IRI-AKI.

Circ_ANKIB1 stabilizes the regulation of miR-19b on SOCS3/STAT3 pathway to promote osteosarcoma cell growth and invasion - Yi-xin Du; Lin-xin Guo; Han-song Pan; Yi-min Liang; Xiang Li (Human Cell, 2020)